Encore for the Enclave: The Changing Nature of the Industry Enclave with Illustrations from the Mining Industry in Chile. (24th January 2015) - Phelps, Nicholas A.; Atienza, Miguel; Arias, Martin
Abstract: Conceptual innovation with respect to the enclave concept has been virtually absent compared with industry agglomerations. This is despite the fact that some varieties of agglomeration distinguished in the literature appear to come close to what previously were regarded as industrial enclaves and despite frequent allusions to the enclave nature of economic spaces produced by contemporary processes of globalization. Bringing the literature on agglomeration and enclaves into dialogue, we revisit the concept of the enclave—a concept that has been largely neglected since it enjoyed a popularity in connection with the study of particular (notably extractive) industries and particular (notably dependencia) theories of national economic development during the 1960s and 1970s. Much has changed since this time, which suggests that the concept of the enclave ought to be ripe for reevaluation. In this article we take an initial step in this direction, identifying analytical dimensions to the enclave and illustrating different manifestations of enclaves in the mining industry, drawing on the case of Chile. We conclude by advocating the renewed study of industry enclaves within contemporary economic geographic analysis.